2002
DOI: 10.1046/j.1365-246x.2002.01830.x
|View full text |Cite
|
Sign up to set email alerts
|

Indication of high pore-fluid pressures in a seismically-active fault zone

Abstract: Summary Polarisations of seismic shear‐wave splitting observed above small earthquakes in Iceland are typically approximately NE to SW, parallel to the direction of maximum horizontal stress. In contrast, the polarisations of shear‐waves at three new stations sited over the Húsavík–Flatey Fault, a major seismically‐active transform fault in northern Iceland, are approximately NW to SE, orthogonal to the stress‐aligned polarisations elsewhere. Modelling suggests that these 90°‐flips in polarisations are caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 22 publications
8
96
0
Order By: Relevance
“…Such cases of up to 90 o -flip above small earthquakes in the vicinity of seismogenic faults has been reported in several studies (e.g. Crampin et al, 2002) that have indicated a key role for over-pressured fluids in the splitting parameters. The presence of over-pressured fluids in the epicentral area of the 2007 seismic swarm and the possible involvement of fluids circulation in depth was suggested by Kassaras et al (2014) as an additional possible scenario for the observed strong stress heterogeneity of the study area.…”
Section: Interpretation and Discussionsupporting
confidence: 52%
“…Such cases of up to 90 o -flip above small earthquakes in the vicinity of seismogenic faults has been reported in several studies (e.g. Crampin et al, 2002) that have indicated a key role for over-pressured fluids in the splitting parameters. The presence of over-pressured fluids in the epicentral area of the 2007 seismic swarm and the possible involvement of fluids circulation in depth was suggested by Kassaras et al (2014) as an additional possible scenario for the observed strong stress heterogeneity of the study area.…”
Section: Interpretation and Discussionsupporting
confidence: 52%
“…[22] A similar mechanism was proposed by Crampin et al [2002] to explain "90°-flips" in . They suggest that as the pore-fluid pressure approaches the maximum horizontal stress and the crack aspect-ratio decreases, the delay times will approach zero.…”
Section: Discussionmentioning
confidence: 74%
“…Similar polarisation anomalies have also been observed in two places above another major fault, the San Andreas Fault in California [42,57]. Modelling the effects with APE, Crampin et al [58,59] shows that the most likely explanation is that the critically high pore-fluid pressures on all seismically active fault planes cause shear-wave polarisations perpendicular to the direction of maximum compressive stress. If normally pressured paths result in positive time-delays, highly pressured paths cause stress-perpendicular first polarisations and hence negative time-delays.…”
Section: • -Flips In Exploration Seismologymentioning
confidence: 65%